Determination of isolation & antibiotic susceptibility pattern of Salmonella spp. from fresh vegetables collected from local markets of Dhaka city - Easrat Jahan, Tonima; Aungshi, Tafannum Faizah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.